Efektivitas Psikoedukasi Berbasis Relaksasi Afirmasi Positif terhadap Penurunan Kecemasan Menjelang Persalinan pada Ibu Hamil di Kelurahan DS - Adelia Putri Ayunda; Rahma Kusumandari (Journal of Innovative and Creativity, 2025)
ABSTRACT The purpose of this study was to examine the effectiveness of a psychoeducation program based on relaxation and positive affirmations in reducing pre-delivery anxiety among pregnant women in DS Village. Materials and Methods. The research employed an experimental method with a Single Group Pretest–Posttest design, involving 15 pregnant women in their first to third trimesters. The instrument used was the Hamilton Anxiety Rating Scale (HARS). The intervention consisted of psychoeducation on prenatal anxiety, deep-breathing relaxation techniques, and positive affirmations. Results of the Paired Sample t-Test indicated a significant decrease in anxiety from the pretest score (M = 26.80) to the posttest score (M = 20.27), p < 0.05. Conclusions. This study concludes that psychoeducation based on relaxation and positive affirmations is effective in reducing prenatal anxiety and can be implemented as a preventive program in public health services, particularly in Pregnancy Classes. Keywords: Effectiveness, Psychoeducation, Prenatal Anxiety, Relaxation, Positive Affirmations